THE EFFECT OF GUIDANCE PROGRAM TO THE CASE STUDY COMPETENCCE OF EDUCATION STUDENTS’ NAKHON PATHOM RAJABHAT UNIVERSITY - Boonmahome, Jesada (Journal of Educational Review Faculty of Education in MCU, 2020)
The purposes of this research article were 1) to compare the capability of the case study with criteria of 80% and 2) to compare the knowledge and attitude of the case study before and after by using the guidance program. A sample group in this research was students of undergraduate education of Nakhon Pathom Rajabhat University; there were 19 members of the sample group whom were obtained by using cluster random sampling. This research was experimental the single group pretest-posttest design. The research instruments were 1) Guidance Program 2) an evaluation form of case study 3) the knowledge test and 4) the attitude test. Statistics used in the research which were Mean, Standard deviation, and t–test. The results of the study were as follows: 1) The capability of the case study after learning by using the guidance program was higher than the set criterion at 80 %. 2) knowledge and attitude of the case study of students after by using the guidance program was higher than that of before with a statistical significance at .05.